The response of the brood pouch transcriptome to synthetic estrogen exposure in the Gulf pipefish (Syngnathus scovelli) - Rose, Emily; Johnson, Bernadette D.; Armitage, Victoria; Jones, Adam G. (Frontiers in Marine Science, 2023)
Endocrine disruptors have devastating impacts on the reproductive physiology of aquatic organisms. The Gulf pipefish, Syngnathus scovelli, is a sexually dimorphic species, which demonstrates predictable morphological, physiological, behavioral, and genetic responses to synthetic estrogen exposure. It has a broad geographic range, spanning freshwater and marine environments, making it a potential sentinel species across a wide range of habitats. In this study, we investigated the effects of ecologically relevant levels of 17α-ethinylestradiol (EE2) exposure on gene expression patterns in the male pipefish’s brood pouch. We also characterized the extent to which EE2-exposed males developed coloration patterns that are normally restricted to females. We identified differentially expressed genes in the brood pouches of pregnant and non-pregnant males when males were exposed to 5ng/L EE2 from the second to eighth day of pregnancy (which normally lasts about 2 weeks). Our result revealed several potential candidate genes that have a role in the brood pouch’s response to environmental estrogens. We also identified genes that were differentially expressed between mid-gestation pregnant males and non-pregnant males. We found an overall greater effect of EE2 exposure in the transcriptomes of non-pregnant males, which may explain why estrogen-exposed males exhibited difficulty receiving eggs in previous studies. The offspring developed similarly in the control and estrogen treatments, highlighting a potential link between the timing of EE2 exposure and its effects on male pregnancy. These results provide insight into how breeding pipefish populations may still exist even though they are found in freshwater and coastal locations where they are periodically exposed to potentially high concentrations of endocrine-disrupting compounds. We also present examples of female-typical coloration development on males due to EE2 exposure and identify candidate brood pouch genes that can be utilized as biomarkers, contributing to the development of the Gulf pipefish as a sentinel model for ecotoxicology.